Description of interpolation spaces for general local Morrey-type spaces - Burenkov, Victor; Darbayeva, Diana; Nursultanov, Erlan (Eurasian Mathematical Journal, 2013)
We consider the real interpolation method and prove that for general local Morrey-type spaces, in the case when they have the same integrability parameter, the interpolation spaces are again general local Morrey-type spaces with appropriately chosen parameters.